2023
DOI: 10.1002/anie.202301607
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Structure and Dynamics of the Squalene‐Hopene Cyclase for (−)‐Ambroxide Production**

Abstract: Terpene cyclases offer enormous synthetic potential, given their unique ability to forge complex hydrocarbon scaffolds from achiral precursors within a single cationic rearrangement cascade. Harnessing their synthetic power, however, has proved to be challenging owing to their generally low catalytic performance. In this study, we unveiled the catalytic potential of the squalene-hopene cyclase (SHC) by harnessing its structure and dynamics. First, we synergistically tailored the active site and entrance tunnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Encouraged by these engineering campaigns, the Hauer group next faced again the intricate cyclization of homofarnesol (15) toward the high-value fragrance ingredient (−)-ambroxan (16). 71 Since no chemical catalyst was able to sufficiently control the stereoselective outcome of this reaction, the SHC equipped with its strongly confined active site served as a potent solution in this regard, which was already recognized by Neumann and Simon as early as 1986. 47 Since the product 16 was the only isomer that crystallized during biotransformation, the authors concluded that the absolute cyclization selectivity toward this single isomer should enhance catalysis because of a shift in chemical equilibrium.…”
Section: ■ Biocatalysis At Basfmentioning
confidence: 99%
See 2 more Smart Citations
“…Encouraged by these engineering campaigns, the Hauer group next faced again the intricate cyclization of homofarnesol (15) toward the high-value fragrance ingredient (−)-ambroxan (16). 71 Since no chemical catalyst was able to sufficiently control the stereoselective outcome of this reaction, the SHC equipped with its strongly confined active site served as a potent solution in this regard, which was already recognized by Neumann and Simon as early as 1986. 47 Since the product 16 was the only isomer that crystallized during biotransformation, the authors concluded that the absolute cyclization selectivity toward this single isomer should enhance catalysis because of a shift in chemical equilibrium.…”
Section: ■ Biocatalysis At Basfmentioning
confidence: 99%
“…(D) Strategies used during the target-oriented engineering campaigns. Adapted with permission from ref . Copyright 2023 Wiley-VCH Verlag GmbH & Co. KGAA.…”
Section: To New Beginningsbernhard′s Time In Stuttgartmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up study, the Hauer group sought to improve the biocatalytic synthesis of (À )-ambrox 1. [41] The researchers re-engineered the active site and entrance tunnel of AacSHC to achieve a 397-fold activity improvement. This study aimed to address the limitations in SHC catalysis through a combination of directed evolution and computational studies.…”
Section: Ionones and Dihydroiononesmentioning
confidence: 99%
“…This knowledge was then harnessed for the synthesis of ( S )‐γ‐dihydroionone, allowing the researchers to produce the complementary fragrance with high enantiomeric excess (>99.9 % ee). In a follow‐up study, the Hauer group sought to improve the biocatalytic synthesis of (−)‐ambrox 1 [41] . The researchers re‐engineered the active site and entrance tunnel of AacSHC to achieve a 397‐fold activity improvement.…”
Section: Sustainable Fragrance Generation Via Industrial Biotechnologymentioning
confidence: 99%